Implementation of dose point kernel (DPK) for dose optimization of 177Lu/90Y cocktail radionuclides in internal dosimetry. (July 2021) - Peer-Firozjaei, Milad; Tajik-Mansoury, Mohammad Ali; Geramifar, Parham; Parach, Ali Asghar; Zarifi, Shiva
Abstract: Background: Due to the importance of choosing the applicable dosimetry method in radionuclide therapy, the present study was conducted to investigate the efficiency of the implementation of Dose Point Kernel (DPK) for dose optimization of 177 Lu/ 90 Y Cocktail Radionuclides in internal Dosimetry. Methods: In this study, simulations and calculations of DPK were performed using the GATE/GEANT4 Monte Carlo code. For specific liver dosimetry, the NCAT phantom and convolution algorithm-based Fast Fourier Transform method was used by MATLAB software. Results: The self-dose of 177 Lu and 90 Y radionuclides in the liver of NCAT phantom were 1.1708E-13, and 4.8420E-11 (Gy/Bq), respectively, and the cross-dose of 177 Lu and 90 Y radionuclides out of the liver of NCAT phantom were 2.03615E-16, and 0.8422E-13 (Gy/Bq) respectively. Overall results showed that with an increase the value of 90 Y with quarter steps in a cocktail, the amount of the self-dose increase 1.5, 6, and 29 times respectively, and with an increase the value of 177 Lu in quarter step in a cocktail, the amount of the cross dose decrease 3, 15 and 68 percent respectively. Conclusion: Generally, the present results indicate that the calculated DPK functions of 177 Lu and 90 Y cocktails can play an important role in choosing the best combination of radionuclide to optimize treatment planning in cocktail radionuclide therapy. Highlights: GATE/GEANT4 dosimetry parameters set and results compare with literature studies. Dose Point Kernel function calculates for 177 Lu and 90 Y separately and in quarter step combination. Internal dosimetry performs by convolution of Dose Point Kernel in activity map. Self-dose and cross-dose of the NCAT liver phantom calculated for cocktail radionuclides. X90 calculated for all combinations of radionuclides.